Military police investigator perspectives of a new self-reflective approach to strengthening resilience: A qualitative study. Issue 5 (3rd September 2019) - Crane, Monique F.; Rapport, Frances; Callen, Joanne; Boga, Danny; Gucciardi, Daniel F.; Sinclair, Laura
ABSTRACT: In this study, we explored participants' experiences of a unique form of resilience training. The aims of this study were to obtain rich information about the participants' experience of the resilience intervention based on adaptive self-reflection, their ability to report the private stress experience and coping efforts when faced with a stressor, their perceptions of training applicability to other contexts, and whether the training was able to encourage the reappraisal of stressors as growth opportunities. A qualitative design was employed with a sample of 21 investigator trainees from the Australian Defence Force School of Policing. Following implementation of the program, trainees provided written responses to seven open ended questions and participated in one focus group designed to embellish understanding of the survey answers. The analysis identified both strengths and limitations in the way respondents were able to recall and report on their private stress experience and coping efforts and several domains where the resilience training seemed to have its effects. Moreover, the respondents reported increased confidence in their ability to manage stressors in the future, recognition of stress in others and the potential to assist them, and a changed view of stress as an opportunity for personal development. Based on these findings, potential improvements in the training materials are recommended. Moreover, the findings suggest coping and emotion regulatory self-reflection may encourage the application of useful strategies and reinforce personal resilient capacities and coping self-efficacy.